Polish press publishers in Piekary near Bytom in the years 1847-1939 - Janusz Wycisło (Folia Historica Cracoviensia, 2008)
The town Piekary played an important role in the years 1847-1939 as one of the first and thriving centres of Polish press in Upper Silesia.